ئاستى زمان لەنێو هۆنراوەکانى حەمەسەعید حەسەن دا - پ.ى د. كوردستان موكريانى (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This paper deals the level of language in the output poetic of the poet Hama Saeed Hassan. This paper shows us the poet has the capability poetic to use such vocabularies and linguistic structures that fit with the issues that deals in his poems. As the poetic image is one of the technical buildings of the poem ingredients, we will conclude the poet had excelled in the images simulations, and snatched similes from the material perceived reality. In addition, the metaphor was another focus in his forms of poetry, which is why taking in metaphors, those words that contribute to the construction of the poetic image. As it is Knows, the subject in all of the poetic, deals those sorts of vocabulary: Betrayal, separation, immigration… all of them, belong to womankind, however, the poet classify himself as a subject in it, but in the shadow of concept non-perception. Add to this, the subject of event, the type of event, and the event time are drafted in the way to highlight his linguistic ability and technical skill. So, all of that, make it him deliver the meaning of meaning and new meanings of words. To sum up, all of above are proof of his linguistic knowledge and ability in the poet